Multiparameter estimation in nonhomogeneous participating slab by using self-organizing migrating algorithms. (May 2015) - Qi, Hong; Niu, Chun-Yang; Jia, Teng; Wang, Da-Lin; Ruan, Li-Ming
Abstract: The self-organizing migrating algorithm (SOMA) and improved SOMA with random mutation (RM-SOMA) were introduced to solve the inverse transient radiation problem. An improved SOMA with random searching (RS-SOMA) was developed on the basis of RM-SOMA by generating a random particle in the searching domain. The time-resolved transmittance and reflectance simulated by the finite-volume method were used as measurement data to estimate the absorption coefficient, scattering coefficient, and geometric positions of the interlayer in a three-layered participating slab exposed to the ultrashort pulse laser by the inverse simulation. The sensitivity of the objective function with respect to the absorption coefficient, scattering coefficient, and geometric positions of the interlayer was also investigated. A comparison among three SOMA methods, i.e., the standard SOMA, RM-SOMA, and RS-SOMA, is presented to illustrate the retrieval performance and accuracy. The effect of measurement errors on the accuracy of estimations by inverse analysis is also examined. All results confirm the potential of the proposed RS-SOMA approach and show its effectiveness and superiority over the other two SOMA algorithms. Unknown radiative parameters can be estimated accurately with RS-SOMA even with noisy data. Furthermore, the absorption coefficient and reduced scattering coefficient are retrieved simultaneously with RS-SOMA by measuring the time-resolved transmittance and reflectance signals of the standard solid imitations exposed to ultrashort pulse laser on the basis of the time-correlated single-photon counting technique. Experimental results show that the parameters can be reasonably estimated by RS-SOMA. In conclusion, the improved RS-SOMA is proven effective and robust. Thus, this method has the potential to be implemented in various fields of inverse radiation problems. Highlights: Three SOMA-based methods were applied to solve inverse transient radiation problem. The synthetical laser incident model can improve the retrieval accuracy. The experimental analyses are presented to prove the performance of the RS-SOMA.